Financial Inclusion in Home Industry of Bamboo Handicrafts in The Trenggalek District - Nugraha, Muhammad Fajar Cahya; Wardoyo, Cipto; Wahyono, Hari (Fakultas Ekonomi, Universitas Negeri Semarang, 2020)
This study aimed to analyze the conditions of financial inclusion in home industry of the bamboo handicrafts and their implications for business performance. The approach used in this research was a qualitative approach, type of case study research. Data collection methods used were interviews and observation. The results of this study indicated that most of the craftsmen were still classified as unbanked people and did not yet have a bank account. The craftsman considered that it was not too important to have a bank account because of the lack of income and low understanding of financial services and products. Significant profit differences made the creation of three classes of craftsmen in the village of Wonoanti. Productivity among craftsmen had a significant difference, caused by the production machines and the number of employees. So, financial inclusion in each craftsman was different. This difference in the level of financial inclusion resulted in differences in business performance between craftsmen classes. The level of financial inclusion was directly proportional to the business performance of each craftsman..